2021
DOI: 10.3389/fimmu.2021.643298
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of T Helper Cells by Tumor Microenvironment in Oral Cancer Is Associated With CCR8 Expression and Rapid Membrane Vitamin D Signaling Pathway

Abstract: The immune system plays a key role in the protective response against oral cancer; however, the tumor microenvironment (TME) impairs this anti-cancer response by modulating T helper (Th) responses and promoting an anti-inflammatory environment. Regulatory T cells (Tregs) and Th2 effector cells (Teff) are associated with poor prognosis in oral squamous cell carcinoma (OSCC). However, the main immunomodulatory mechanisms associated with the enrichment of these subsets in OSCC remain unknown. We characterized Th-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 68 publications
1
9
1
Order By: Relevance
“…There is convincing evidence in the literature that vitamin D is able to affect cancer progression at several levels by affecting tumor microenvironment composition consequently reducing cancer cell growth, inhibiting angiogenesis, and interfering with metastatic processes ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is convincing evidence in the literature that vitamin D is able to affect cancer progression at several levels by affecting tumor microenvironment composition consequently reducing cancer cell growth, inhibiting angiogenesis, and interfering with metastatic processes ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that RAD51AP1 expression was significantly positively correlated with the infiltration levels of Th2 cells, T helper cells and Treg cells. Th2 cells and Treg cells were considered as the oncogenic immune cells implicated in several types of tumors [23][24][25][26]. For example, the infiltration of Th2 cells promote tumor progression, and significantly correlates with poor survival in pancreatic cancer [27].…”
Section: Discussionmentioning
confidence: 99%
“…After performing a mycoplasma, test a proteomic analysis was conducted in four different representative hWJCM samples. Briefly, the protein content of each sample was purified and quantified in order to obtain 200 ng of secretome tryptic peptides to be performed by LS‐MS/MS 57 . Protein interaction networks were identified with STRING database helper to visualize a core analysis of the immunology biological functions 58…”
Section: Methodsmentioning
confidence: 99%